2003
DOI: 10.1139/w03-073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bacterial strains isolated from lead-polluted soil and their interactions with arbuscular mycorrhizae on the growth of Trifolium pratense L. under lead toxicity

Abstract: We isolated two bacterial strains from an experimentally lead (Pb)-polluted soil in Hungary, 10 years after soil contamination. These strains represented the two most abundant cultivable bacterial groups in such soil, and we tested their influence on Trifolium pratense L. growth and on the functioning of native mycorrhizal fungi under Pb toxicity in a second Pb-spiked soil. Our results showed that bacterial strain A enhanced plant growth, nitrogen and phosphorus accumulations, nodule formation, and mycorrhizal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 51 publications
2
50
0
3
Order By: Relevance
“…Sannazzora et al (2005) reported that plants inoculated with Glomus intraradices had higher chlorophyll density than non-mycorrhiza inoculated plants. Vivas et al (2003) showed that inoculation of bacterial strain increased chlorophyll content of lettuce when compared to control. Apparently zinc is involved in the production of chlorophyll.…”
Section: Chlorophyll Contentmentioning
confidence: 97%
See 1 more Smart Citation
“…Sannazzora et al (2005) reported that plants inoculated with Glomus intraradices had higher chlorophyll density than non-mycorrhiza inoculated plants. Vivas et al (2003) showed that inoculation of bacterial strain increased chlorophyll content of lettuce when compared to control. Apparently zinc is involved in the production of chlorophyll.…”
Section: Chlorophyll Contentmentioning
confidence: 97%
“…Azcon and Barea (2010) have been proposed co-inoculation PGPR and AM fungi as an efficient procedure to increase yield and plant growth. Vivas et al (2003) suggested that there are synergistic effects on plant growth when bacteria (PGPR) and AM fungi are inoculated, particularly under growth-limited conditions. Many researchers have indicated that bio fertilizers can alleviate the unfavorable effects of drought stress on plant growth (Khalafallah and Abo-Ghalia 2008).…”
Section: Grain Yieldmentioning
confidence: 99%
“…inoculation with bio fertilizer as an efficient procedure to increase plant growth. Vivas et al (2003) suggested that there are synergistic effects on plant growth when PGPR and mycorrhiza are inoculated, particularly under growth limited conditions.…”
Section: Grain Yieldmentioning
confidence: 99%
“…The authors wish to thank the Editor-in-Chief and the three anonymous reviewers for this Thlaspi caerulescens Thlaspi ochroleucum Fabacceae Pisum sativum Trifolium pratense Chen & al., 2003;Bi & al., 2003;Vivas & al., 2003 Trifolium repense Li & Christie, 2001; Poaceae Andropogon virginicus Hordeum vulgare Lolium perenne Li & Christie, 2001; Triticum aestivum Zea mays Chen & al., 2004a,b Solanaceae Nicotiana glauca Nicotiana rustica Audet & Charest, 2006 Supplementary Data -2…”
Section: Acknowledgementsmentioning
confidence: 99%